Advancing Positioning, Navigation, and Timing (PNT) Service Using Satellite Navigation Technology (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This Reprint aims to comprehensively explore the expansive and ever-evolving realm of Positioning, Navigation, and Timing (PNT) technologies, with a primary focus on those rooted in satellite navigation systems. It serves as an in-depth platform for delving into a wide array of significant topics, including, but not limited to, the seamless integration of multiple PNT sources for enhanced accuracy and reliability, the development of resilient PNT systems capable of withstanding challenging environments, miniaturized micro PNT innovations tailored for small-scale devices, secure PNT frameworks to safeguard against cyber threats, advancements in GNSS Precise Point Positioning (PPP) and PPP-Real-Time Kinematic (PPP-RTK) for centimeter-level real-time positioning, precision in GNSS timing for critical applications, refined GNSS orbit determination and modeling for improved system performance, atmospheric sensing utilizing GNSS signals for weather forecasting, research into the impact of ionospheric disturbances and space weather on GNSS signals, and the integration of navigation with smart applications, as well as exploring satellite navigation countermeasures and the future potential of Low-Earth-Orbit (LEO) PNT and broadband PNT constellations leveraging signals of opportunity.